1988
DOI: 10.1111/j.1365-2621.1988.tb07716.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Temperature and Time on the Quality of Vacuum Packaged Dry‐Cured Ham Slices

Abstract: Hams were cured and aged by three methods, two using nitrite and nitrate but with long or short aging times at controlled temperature, and one using no nitrite or nitrate with ambient aging temperature. Hams were sliced, vacuum-packaged and stored at O"C, 10°C or 21°C for 8 wk and examined weekly for white film, aroma, and aerobic, staphylococci, lactobacilli, yeast and mold counts. White film development was erratic. Aroma was closely related to aerobic counts. At 0°C bacterial counts and aroma remained norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The higher yeasts and mold counts at 2°C may be due to less competition from bacterial growth or to production of compounds by lactobacilli which are inhibitory to yeasts and molds at 24°C. In previous work, Kemp et al (1988) found initial counts similar to those in this study but neither time nor temperatures greatly affected counts, although in one trial counts were lower in slices stored at a higher temperature.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The higher yeasts and mold counts at 2°C may be due to less competition from bacterial growth or to production of compounds by lactobacilli which are inhibitory to yeasts and molds at 24°C. In previous work, Kemp et al (1988) found initial counts similar to those in this study but neither time nor temperatures greatly affected counts, although in one trial counts were lower in slices stored at a higher temperature.…”
Section: Resultssupporting
confidence: 84%
“…THE ADVANTAGE of low temperature storage on dry-cured vacuum-packaged country ham slices was demonstrated by Kemp et. al.…”
Section: Introductionmentioning
confidence: 96%
“…Commercialisation of sliced and packaged dry-cured Iberian ham is becoming more and more important. Quality characteristics of dry-cured meat products easily deteriorate after slicing, due to discoloration of the surface, moisture loss and rancid flavour development (Kemp et al, 1988;Ventanas et al, 2001), all these phenomena being related with lipid oxidation. Low deterioration of ␣-tocopherol during the processing of dry-cured hams has been reported (Isabel et al, 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…Nassos et al (1983Nassos et al ( , 1985 reported significant correlations between pH, lactic acid concentrations and odor acceptability, and between pH, lactic acid and Gram-positive bacteria in refrigerated ground beef stored in oxygen-impermeable packaging. Sensory scores for aroma have been closely related to aerobic bacterial counts in vacuum-packaged pork products (Kemp et al 1988). Alternative environments in the vacuum package that would suppress growth of spoilage microbes while maintaining product color would be most beneficial.…”
Section: Introductionmentioning
confidence: 99%